TINGKAT KESESUAIAN SUAKA MARGASATWA CIKEPUH SEBAGAI HABITAT KEDUA BADAK JAWA (Rhinoceros sondaicus Desmarest, 1822) - Ribai .; Hadi S Alikodra; Burhanuddin Masyud; U Mamat Rahmat (Department of Forest Resources Conservation and Ecotourism - IPB University, 2015)
Javan rhino (Rhinoceros sondaicus) is one of the rarest species in the world so categorized as critically endangered by IUCN. Survival of the rhino in Ujung Kulon National Park is threatened by a variety of factors that could cause these extinct animals, such as: invasion langkap, competition with the bulls, and inbreeding. The strategy should be promoted in maintaining and developing population that is making a second habitat. The purpose of this research is to know the suitability level of Cikepuh Wildlife Reserves (CWR) as javan rhino’s second habitat. The method used is the field observations. Results showed that the CWR have high suitability as javan rhino’s second habitat with an area of 6886.4 ha (84.72% CWR). Cikepuh Wildlife Reserves components that have a high potential as second habitat are on aspects altitude, air temperature, humidity, water availability, and soil pH. Strategies that can be done in improving the suitability of the CWR as second habitat includ: create pools ofthe rhino, planting food plants that have a high palatability and reduce human pressure through strict enforcement, public education, standardized regular patrols, rehabilitation and enrichment of degraded area, livestock expenses , and review the MoU regarding the use of the area as a military Cikepuh SM. Keywords: Cikepuh Wildlife Reserve, habitat suitability, javan rhino, second habitat